ASSA14-03-08 Gastrin and D1 Dopamine Receptor Interact to Induce Natriuresis and Diuresis. (1st December 2014) - Chen, Y; Asico, LD; Zheng, S; Villar, VAM; He, D; Zhou, L; Zeng, C; Jose, PA
Abstract : Objective: Oral NaCl intake produces stronger natriuresis and diuresis than venous infusion of same amount, indicating the existence of renal-gastric axis. Gastrin, from gastrointestinal tract, is dominant one due to its natriuretic effects and taken-up by the renal proximal tubule (RPT) cells. We hypothesise that gastrin interact with dopamine receptors in kidney, resulting in synergistically increased sodium excretion. The impaired interaction might be involved in hypertension. Method: Wistar-Kyoto (WKY) rats, spontaneously hypertensive rats (SHR) and RPT cells were stimulated or blocked through D1 -like dopamine and gastrin receptors to observe Na + -K + -ATPase activity and natriuresis. Result: Gastrin infusing WKY rats via renal artery induced natriuresis and diuresis, which was blocked in the presence of CI988, a gastrin receptor blocker. Similarly, effect hereinbefore of fenoldopam, a D1 -like receptor agonist, was blocked by D1 -like receptor antagonist, SCH23390, indicating gastrin and fenoldopam play natriuretic and diuretic effect through individual receptors. Lower dosages of gastrin or fenoldopam failed to induce natriuresis and diuresis alone, while putting together induced the effects. The above-mentioned effects were lost in SHRs. Natriuresis and diuresis was partially blocked by SCH23390 or CI988, indicating the interaction between gastrin and D1-like receptor. Stimulation of either receptor increased the expression of the other and inhibited Na + -K + -ATPase activity, while the inhibitory effect of Na + -K + -ATPase activity was partially blocked through its corresponding receptors due to respective existence of SCH23390 and CI988. Conclusion: It indicated the synergistic effect between gastrin and D1-like receptor would increase the sodium excretion in WKY rats; the impaired interaction might be involved in the pathogenesis of hypertension.